Right and left heart function in lowlanders with COPD at altitude: Data from a Randomized Study - Lichtblau, Mona; Latshang, Tsogyal D.; Furian, Michael; Müller-Mottet, Séverine; Küest, Silke; Tanner, Felix; Grünig, Ekkehard; Bloch, Konrad E.; Ulrich, Silvia (Respiration, 2019)
Background: Changes in pulmonary hemodynamics and cardiac function in patients with chronic obstructive pulmonary disease (COPD) traveling to altitude have not been assessed despite an increasing prevalence of the disease. Objectives: We hypothesized that pulmonary artery pressure (PAP) significantly increases and cardiac function deteriorates during exposure to hypobaric hypoxia as encountered by traveling to moderate altitude or air flight. Methods: A total of 37 patients (17 female; median age [quartiles] 66 years [60; 69] with COPD GOLD grade 2-3 [FEV1 57% predicted (49; 71)]) living < 800 m underwent echocardiography in Zurich (490 m) and after 1 night at Davos Jakobshorn (2,590 m) in a randomized order of allocation. Results: The transtricuspid pressure gradient increased from 23 mm Hg (18; 29) to 32 mm Hg (25; 41) (p < 0.0001; Δmedian [95% CI] 7.5 [2.0; 13.0]), the right ventricular fractional area change decreased from 45% (39; 49) to 38% (33; 43) (p = 0.002), while the heart rate and systolic blood pressure increased from 70 bpm (64; 78) to 82 bpm (70; 86) (p < 0.0001) and from 133 mm Hg (123; 141) to 136 mm Hg (126; 148) (p = 0.002), respectively, and left ventricular diastolic dysfunction was more prevalent (24-54%, p = 0.02). Conclusions: This is a first study assessing changes in pulmonary hemodynamics and cardiac function in patients with COPD during a short altitude sojourn. Despite the increase in PAP and indications of change in cardiac function, the exposure was well tolerated. None of the patients had to descend to lower altitude for symptomatic altitude-related disease.
Gesehen am 27.06.2019